Remarkable Improvement in Photocatalytic Performance for Tannery Wastewater Processing via SnS2 Modified with N‐Doped Carbon Quantum Dots: Synthesis, Characterization, and 4‐Nitrophenol‐Aided Cr(VI) Photoreduction. Issue 29 (8th February 2019) - Wang, Shuo; Li, Liping; Zhu, Zhenghui; Zhao, Minglei; Zhang, Liming; Zhang, Nannan; Wu, Qiannan; Wang, Xiyang; Li, Guangshe
Abstract: Photocatalytic pathways are proved crucial for the sustainable production of chemicals and fuels required for a pollution‐free planet. Electron–hole recombination is a critical problem that has, so far, limited the efficiency of the most promising photocatalytic materials. Here, the efficacy of the 0D N doped carbon quantum dots (N‐CQDs) is demonstrated in accelerating the charge separation and transfer and thereby boosting the activity of a narrow‐bandgap SnS2 photocatalytic system. N‐CQDs are in situ loaded onto SnS2 nanosheets in forming N‐CQDs/SnS2 composite via an electrostatic interaction under hydrothermal conditions. Cr(VI) photoreduction rate of N‐CQDs/SnS2 is highly enhanced by engineering the loading contents of N‐CQDs, in which the optimal N‐CQDs/SnS2 with 40 mol% N‐CQDs exhibits a remarkable Cr(VI) photoreduction rate of 0.148 min −1, about 5‐time and 148‐time higher than that of SnS2 and N‐CQDs, respectively. Examining the photoexcited charges via zeta potential, X‐ray photoelectron spectroscopy (XPS), surface photovoltage, and electrochemical impedance spectra indicate that the improved Cr(VI) photodegradation rate is linked to the strong electrostatic attraction between N‐CQDs and SnS2 nanosheets in composite, which favors efficient carrier utilization. To further boost the carrier utilization, 4‐nitrophenol is introduced in this photocatalytic system and the efficiency of Cr(VI) photoreduction is further promoted. Abstract : 0D N‐doped carbon quantum dots (N23 ‐CQDs) are demonstrated in accelerating the charge separation and transfer and thereby boosting the activity of a narrow‐bandgap SnS2 . To promote carrier utilization, 4‐nitrophenol is taken as hole acceptor, and the efficiency of Cr(VI) photoreduction is further enhanced.